2013
DOI: 10.1002/adv.21354
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Preparation Method for Octreotide Acetate–Loaded PLGA Microspheres with a High Drug‐Loading Capacity and a Low Initial Burst Release, and Its Studies on Relations between In Vitro and In Vivo Release

Abstract: ABSTRACT:In this study, octreotide acetate (OTA)-loaded poly(lactide-co-glycolide) (PLGA) microspheres were prepared using an optimized double emulsion solvent evaporation method. The loading capacity (LC) was increased by raising the concentration of OTA in the inner aqueous phase (W1), and burst release was decreased (<10.0%) because the higher viscosity hindered the diffusion of OTA. The in vitro release profiles were closely correlated with in vivo release profiles calculated using the Wagner-Nelson method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, the appropriate amount of Octreotide reference substance was determined accurately, and the diluted solution was added in the same way to prepare a 50 μg/ml solution. The content of Octreotide acetate in the sample was calculated from the peak area according to the external standard method (Zhang et al., 2010 ; Chen et al., 2014 ). Microspheres were dispersed in 0.1% (w/w) Tween 20 aqueous solution, and the particle size was measured by a Mastersizer 2000 particle analyzer (Malvern, England).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the appropriate amount of Octreotide reference substance was determined accurately, and the diluted solution was added in the same way to prepare a 50 μg/ml solution. The content of Octreotide acetate in the sample was calculated from the peak area according to the external standard method (Zhang et al., 2010 ; Chen et al., 2014 ). Microspheres were dispersed in 0.1% (w/w) Tween 20 aqueous solution, and the particle size was measured by a Mastersizer 2000 particle analyzer (Malvern, England).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that there were significant difference in drug release behavior and distribution of microspheres with different mixed solvents. PLGA microspheres supported by Octreotide were prepared to increase the concentration of Octreotide in internal aqueous phase (Chen et al., 2014 ). At the same time, cracking was further reduced by changing the proportion of organic solvents.…”
Section: Introductionmentioning
confidence: 99%